Sistem Pola Asuh Orang Tua dalam Pendidikan Islam di Masyarakat Perkotaan dan Pedesaan - Salsabila, Annida; Anita Puspita Julianti; Laisha Zahra Irawan; Naimah Nurtsania; Hafiziani Eka Putri; Hisny Fajrussalam (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
The parenting system has a significant influence on children’s development, especially in Islamic Education, which emphasizes discipline and responsibility. This study aims to analyze the differences in parenting systems between urban and rural communities and their impact on children’s Islamic Education. A quantitative approach with descriptive survey method was used in this study, involving 40 participants, consisting of 20 urban and 20 rural parents. Data were collected through questionnaires and analyzed using statistical test, including normality test and Mann-Whitney U test. The result showed that there was no significant difference between parenting in urban and rural communities. Although there are differences in methods, such as the use of technology in urban areas and extended family involvement in rural areas. The overall of communication and parental involvement in supporting children’s religious education in both urban and rural settings.